Analisis Kemampuan Pemecahan Masalah Matematika Siswa SMA pada Kurikulum Merdeka dan Kurikulum 2013 Berdasarkan Teori Polya - Maulana, Septian Dika; Santosa, Cecep Anwar Hadi Firdos (Jurnal Pendidikan Matematika : Judika Education, 2024)
This research aims to analyze students' mathematical problem solving abilities in schools that implement the independent curriculum and the 2013 curriculum, based on Polya theory. The research method used is a qualitative method. The results of the research show that class Meanwhile, class The conclusion that can be drawn is that students who study with the independent curriculum have low problem solving abilities, seen from the students' inability to complete each step of solving Polya. Meanwhile, students who study with the 2013 curriculum have good problem solving abilities, seen from several students who can solve problems using Polya steps well. The conclusion that can be drawn is that students who study with the independent curriculum have low problem solving abilities, seen from the students' inability to complete each step of solving Polya. Meanwhile, students who study with the 2013 curriculum have good problem solving abilities, seen from several students who can solve problems using Polya steps well. Keywords: 2013 Curriculum, Independent Curriculum, Problem Solving